Prognosis Uji Jalan 6 Menit Terhadap Kejadian Kardiovaskular atau Mortalitas Pasien Kardiovaskular - Angela, Devina; Tedjasukmana, Deddy (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction In performing activities, individuals require submaximal aerobic metabolism which is an integrated effort of the respiratory, cardiovascular and skeletal muscle systems that will determine functional capacity.1,2 Disorders of the heart and vascular system that supply oxygen can lead to impaired functional capacity. Low functional capacity is associated with an increased risk of mortality, especially cardiovascular disease.3 In Indonesia, cardiovascular disease is the second leading cause of morbidity and mortality, responsible for one third of all deaths in Indonesia.4 Functional capacity assessment can provide diagnostic information, pretreatment and posttreatment comparisons, and predictors of morbidity and mortality in patients with cardiovascular disease and various clinical conditions.2,5